A hipótese-cinema: escola, produção audiovisual e ensino de História - Pinto, Jonas Tadeu Amaral [UNIFESP] (2019)
This paper aims to analyse the possibilities raised by the relationship among cinema, school and the teaching of History through a perspective in which learners can have the leading role in the production of knowledge. Accordingly, it proposes a pedagogical practice that develops the education of critical observation with students, who start to notice films as a historical document, a cultural product, and an artistic creation, also ensuring the cultural broadening of the involved groups. The given analysis demonstrates that such process is understood by the own development of History in its school subject status, within school cultures (JÚLIA, 2001 e VIÑAO, 2007). Considering cinema in the sense of otherness (BERGALA 2008, FRESQUET 2013, MIGLORIN 2015), the experiences resulted from an audiovisual production in the school environment was initially adopted, based on the difficulties, tensions and awkwardness that such a process created in the Profª Virginia Loriza Zeitounian Camargo municipal school. Within it, tools to map the organisation forms and sharing of the sensitive (RANCIERE, 2005) were used to find potentials, breaches in the structure of the organisation of the common space, thus making the work with cinema focused otherness possible. The realisation of creation devices and picture capturing were proposed to play a part in the development of own concepts to the teaching of history, time and narrative, besides provoking a new organisation of the sensitive. Therefore, it is hoped that a contribution to the reflection upon the challenges and potentialities of school audiovisual production in the teaching of History through specific school cultures is provided.